(untitled) (Eurasian Medical Research Periodical, 2023)
One of the public health challenges is the control of Crimean-Congo hemorrhagic fever (CCHF), as this viral zoonotic disease infected both animals and humans, sometimes leading to death. Re-emergence of this endemic in some regions, such as our country, to the need for more documented information and facts about it, Iraq, has led transmitted, infected, and prevent it. Therefore, this review aimed to summarize main information about this infection. The causative virus consists of a globular RNA genome particle with a segmented negative sense encapsulated in a lipid structure containing or direct contact with infected viral glycoproteins. Infection usually occurs by ticks human or animal tissue or blood. The causative virus has a high ability to transmit in Infection in areas with mammals, whether large or small, such as rabbits and cattle. animals is asymptomatic, while in peoples it is manifested by high fever and ends with hemorrhagic syndrome. It is recommended to implement preventive measures to control tick vectors in endemic countries, and to encourage collaboration between clinical veterinary, physicians and ecologists’ researchers